Persistent Supercooled Drizzle at Temperatures below −25°C Observed at McMurdo Station, Antarctica - Silber, Israel (J Geophys Res Atmos, 2019)
The rarity of reports in the literature of brief and spatially limited observations of drizzle at temperatures below −20°C suggest that riming and other temperature-dependent cloud microphysical processes such as heterogeneous ice nucleation and ice crystal depositional growth prevent drizzle persistence in cold environments. In this study, we report on a persistent drizzle event observed by ground-based remote-sensing measurements at McMurdo Station, Antarctica. The temperatures in the drizzle-producing cloud were below −25°C and the drizzle persisted for a period exceeding 7.5 hours. Using ground-based, satellite, and reanalysis data we conclude that drizzle was likely present in parts of a widespread cloud field, which stretched more than ~1000 km along the Ross Ice Shelf coast. Parameter space sensitivity tests using two-moment bulk microphysics in large-eddy simulations constrained by the observations suggest that activated ice freezing nuclei (IFN) and accumulation-mode aerosol number concentrations aloft during this persistent drizzle period were likely on the order of 0.2 L(−1) and 20 cm(−3), respectively. In such constrained simulations, the drizzle moisture flux through cloud base exceeds that of ice. The simulations also indicate that drizzle can lead to the formation of multiple peaks in cloud water content profiles. This study suggests that persistent drizzle at these low temperatures may be common at the low aerosol concentrations typical of the Antarctic and Southern Ocean atmospheres.